2017
DOI: 10.1111/cge.13022
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide linkage and sequence analysis challenge CCDC66 as a human retinal dystrophy candidate gene and support a distinct NMNAT1‐related fundus phenotype

Abstract: Funding informationStiftung Auge (Deutsche Ophthalmologische Gesellschaft, DOG.To uncover the genotype underlying early-onset cone-rod dystrophy and central nummular macular atrophic lesion in 2 siblings from an endogamous Arab family, we performed targeted next-generation sequencing (NGS) of 44 retinal dystrophy genes, whole-exome sequencing (WES) and genome-wide linkage analysis. Targeted NGS and WES in the index patient highlighted 2 homozygous variants, a CCDC66 frameshift deletion and a novel missense NMN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Our findings indicate that the homozygous variant in Case 1, initially reported as "inconclusive", is significant and should not be ignored, and that the NMNAT1 variants in Case 2 are causative of the disease phenotype. This is further supported by the recent report of two siblings with a homozygous NMNAT1 variant c.[500A > G] p.(Asn167Ser) who had a clinical diagnosis of CRD with atrophic macular changes [21]. This affects clinical management, especially for adult cases where there may be a consanguineous union, heralding the need for investigation for the variant in the partner, since presence would indicate a 50% recurrence risk.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings indicate that the homozygous variant in Case 1, initially reported as "inconclusive", is significant and should not be ignored, and that the NMNAT1 variants in Case 2 are causative of the disease phenotype. This is further supported by the recent report of two siblings with a homozygous NMNAT1 variant c.[500A > G] p.(Asn167Ser) who had a clinical diagnosis of CRD with atrophic macular changes [21]. This affects clinical management, especially for adult cases where there may be a consanguineous union, heralding the need for investigation for the variant in the partner, since presence would indicate a 50% recurrence risk.…”
Section: Discussionmentioning
confidence: 70%
“…NMNAT1 is a nuclear enzyme that synthesizes NAD + , an essential metabolite that is central to all aspects of cellular metabolism. NMNAT1 is indispensable for mouse development ( Conforti et al, 2011 ) and recent studies identified causative mutations in NMNAT1 in patients with Leber congenital amaurosis type 9 (LCA9), a disorder associated with severe, early-onset retinal degeneration and vision loss ( Falk et al, 2012 ; Perrault et al, 2012 ; Koenekoop et al, 2012 ; Chiang et al, 2012 ; Coppieters et al, 2015 ; Khan et al, 2018 ). Patients with LCA9 have no systemic involvement outside the eye, suggesting that certain cells within the retina are particularly vulnerable to the loss of NMNAT1 function.…”
Section: Resultsmentioning
confidence: 99%
“…LCA is the most common cause of blindness in children and about 70% of LCA cases are associated with mutations in genes related to the visual cycle, cGMP production, ciliogenesis, or transcription. Recently, more than thirty mutations in the nuclear NAD + biosynthetic enzyme NMNAT1 were identified in patients with autosomal recessive LCA type 9 (LCA9) ( Falk et al, 2012 ; Perrault et al, 2012 ; Koenekoop et al, 2012 ; Chiang et al, 2012 ; Coppieters et al, 2015 ; Khan et al, 2018 ). Despite the ubiquitous expression of this key NAD + biosynthesis enzyme, LCA9 patients have no other systemic deficits outside the retina.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 80 RP and 20 Leber congenital amaurosis patients no pathogenic variant has been found ( Gerding et al, 2011 ). In addition, a homozygous missense mutation in the CCDC66 gene was recently excluded by linkage and segregation analysis to be disease causing in two Arabian siblings with retinal dystrophy, or in this particular type of retinal degeneration ( Khan et al, 2018 ). The more precise description of the Ccdc66 -/- mouse may allow to predict defined groups of patients with retinal degeneration of unknown cause (besides RP) that might be promising candidates to be tested for CCDC66 mutation in order to identify disease-causing mutations in humans.…”
Section: Discussionmentioning
confidence: 99%